PENINGKATAN KEMAMPUAN PASSING ATAS PADA PERMAINAN BOLA VOLI DENGAN MENGGUNAKAN MEDIA BOLA GANTUNG PADA SISWA KELAS VII SMP NEGERI SATAP SALUSIMBUANG - Saiful, Akbar; Nur, Suaib; A. Heri Riswanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of overhead passing skills on volleyball in seventh-grade students at Satap Salusimbuang Public Junior High School. This study was an experimental study. The subjects were 21 seventh-grade students at Satap Salusimbuang Public Junior High School. The data collection technique used was an overhead passing skill test. The results showed that the use of hanging balls influenced students' overhead passing skills in volleyball in seventh-grade students at Satap Salusimbuang Public Junior High School. Based on the Paired Sample T-test data, a p-value of 0.001 was obtained with an α value of 0.05. Thus, it is clear that the p value (0.001) < α (0.05), so H0 is rejected so it can be concluded that there is an increase in students' passing ability after using hanging ball media in class VII at SMP Negeri Satap Salusimbuang.